Semiotics and visual communication II : culture of seduction - Zantides, Evripides (Cambridge Scholars Publishing, 2017)
The chapters in this book consist of selected papers that were presented at the 2nd International Conference and Poster Exhibition on Semiotics and Visual Communication at the Cyprus University of Technology in October 2015. They investigate the theme of the Conference, Culture of Seduction [the seduction of culture] and look at Seduction as in deception, not sexual enticement, but as a mechanism of attraction and appeal which has often been the case in many communication strategies and approaches used by mass and popular culture. Seduction has historic and increasing agency in visual communication -- the urgency to entice viewers is ever more powerful in difficult economic times, in an increasingly hyper-real world -- and designers are led to become exceedingly complicit in its strategies. The contributions here cover a range of approaches from theoretical aspects of seduction in verbal and nonverbal communication, public spaces, design and meaning, seductive strategies, and advertising design, as well as fashion representations and packaging design.